Understanding naturalism - Ritchie, Jack (Understanding movements in modern thought., 2014)
Naturalist ideas in epistemology, metaphysics and philosophy of language have been some of the most influential in recent philosophy, yet there exists no introduction to naturalism as a distinct philosophical position. This book is it. Many contemporary Anglo-American philosophers describe themselves as naturalists. But what do they mean by that term? Popular naturalist slogans like, #x93;there is no first philosophy#x94; or #x93;philosophy is continuous with the natural sciences#x94; are far from illuminating. Understanding Naturalism provides a clear and readable survey of the main strands in recent naturalist thought. The origin and development of naturalist ideas in epistemology, metaphysics and semantics is explained through the works of Quine, Goldman, Kuhn, Chalmers, Papineau, Millikan and others. Key objections to naturalism, such as it fails to engage with #x93;real#x94; philosophical problems, it is self-refuting, and it cannot deal with normative notions like truth, justification and meaning, are all addressed. Ritchie distinguishes two strands of naturalist thinking #x96; the constructive and the deflationary #x96; and shows how this distinction can invigorate naturalism and the future of philosophical research.